2018
DOI: 10.3389/fimmu.2018.00805
|View full text |Cite
|
Sign up to set email alerts
|

Follicular Dendritic Cells of Lymph Nodes as Human Immunodeficiency Virus/Simian Immunodeficiency Virus Reservoirs and Insights on Cervical Lymph Node

Abstract: A hallmark feature of follicular dendritic cells (FDCs) within the lymph nodes (LNs) is their ability to retain antigens and virions for a prolonged duration. FDCs in the cervical lymph nodes (CLNs) are particularly relevant in elucidating human immunodeficiency virus (HIV)-1 infection within the cerebrospinal fluid (CSF) draining LNs of the central nervous system. The FDC viral reservoir in both peripheral LN and CLN, like the other HIV reservoirs, contribute to both low-level viremia and viral resurgence upo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 110 publications
1
13
0
Order By: Relevance
“…Recent studies have reported the critical role of FDCs in chronic infectious diseases. Importantly, FDCs are a critical HIV reservoir where FDCs-trapped HIV persists for long periods, resulting in the perpetuation and reignition of the disease [29][30][31]. FDCs also play an essential role in autoimmune disorders, which frequently display follicles with ICs-bearing FDCs, autoreactive GCs, and ongoing a nity maturation [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported the critical role of FDCs in chronic infectious diseases. Importantly, FDCs are a critical HIV reservoir where FDCs-trapped HIV persists for long periods, resulting in the perpetuation and reignition of the disease [29][30][31]. FDCs also play an essential role in autoimmune disorders, which frequently display follicles with ICs-bearing FDCs, autoreactive GCs, and ongoing a nity maturation [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported the critical role of FDCs in chronic infectious diseases. Importantly, FDCs are a critical HIV reservoir in which FDC-trapped HIV persists for long periods, resulting in the perpetuation and reignition of the disease [31][32][33]. FDCs also play an essential role in autoimmune disorders, which frequently display follicles with ICs-bearing FDCs, autoreactive GCs, and ongoing a nity maturation [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…As described above, CSF and ISF exchange occurs in the peri-venous space and ISF is then transported from the brain to the cervical lymph nodes ( Figure 2 ; Iliff et al, 2013 ). Cervical lymph nodes (CLNs) are a group of lymph nodes in the neck region that are located adjacent to the cervical region of the spinal cord near the sternocleidomastoid muscle (Dave et al, 2018a ). The glymphatic and meningeal systems function as a waste removal pathway by connecting the CNS to the CLNs (Benveniste et al, 2017 ).…”
Section: Cervical Lymph Nodes As a Reservoir For Hivmentioning
confidence: 99%
“…T cells and antigen-presenting cells (APCs) that are present within the CNS drain via the lymphatic path into the CLNs (Benveniste et al, 2017 ). CLNs contain follicular dendritic cells (FDCs) which can retain antigens for a prolonged duration allowing them to potentially act as a reservoir for HIV (Sabri et al, 2016 ; Dave et al, 2018a ). FDCs are important for immune function as they allow for germinal center formation, long term immune recovery (Dave et al, 2018a , b ) and may contribute significantly to immune system response to the virus, the viral reservoir and escape.…”
Section: Cervical Lymph Nodes As a Reservoir For Hivmentioning
confidence: 99%
See 1 more Smart Citation